of Mergers and Acquisitions on the Human Resource Department - mohatta, maulshree (2007)
Mergers and acquisitions take place in all forms of industries and businesses, however small or large. They have and impact on almost all the areas and departments of business. One department in any business or industry on which a merger or an acquisition has a major impact is the human recourse department or the personnel of the companies which have undergone a merger, or have acquired, or have been acquired. The following dissertation represents an analysis of the research carried out on the impact of a merger and acquisition on human resource. Because change management in a merger and acquisition environment represents a notable challenge for the organization, there is a direct impetus to consider how human resource management teams can work to mitigate the problems that can arise in this environment. Primary as well as secondary research was carried out to support and validate the data that helped arrive at the analysis and conclusion of this study. Secondary data is supported by journals and articles, whereas primary data is collected by ways of questionnaires. The study has been presented in chapter form, where each chapter has been defined and different areas and aspects have been covered under separate titles. Chapter 1 gives an insight of the companies on which the research has been carried out. The second is the literature review, which talks about what the scholars have to say about mergers and acquisitions, and also explains the steps and the problems, etc. Following this is the research methodology, which deals with the qualitative and the quantitative methods used, questionnaire design and limitations of the research. The forth chapter talks about the impact of the merger and acquisition on the three companies involved and the areas affected, but most primarily, the human resource department. Chapter five is the analysis of the data collected from the employees of the companies. The last chapter, is the conclusions and discussions, along with suggestions, which agree that the human resource department plays vital role in the success of any merger or acquisition.